(untitled) (Buana Pendidikan: Jurnal Fakultas Keguruan dan Ilmu Pendidikan Unipa Surabaya, 2020)
This current study aims at observing the influence of pre-exercise sport massage therapy towards the cultivation of agility to the football player of Universitas Tunas Pembangunan Surakarta. This study has been accomplished in 18 weeks. The population of the study is all of the football player of UTP Surakarta. The samples are 28 athletes. Based on the prerequisite test result, the normality test of the pretest group experiment is at 0,130, the post-test group experiment is at 0,161, the controlled pre-test is at 0,187, the controlled post-test is at 0,168. Based on the normality test, it can be concluded that all of the data are at 0,05 which means that the data distributes the normal frequency. Based on the homogeneity test, this study shows at 0,53 where the data depicts above 0,05, hence the data are homogeny. Based on the result of hypothesis test towards the pre-test and post-test experiment, it can be concluded that the significance level is at 0,328 > 0,05, therefore the null hypothesis which reflects “there are no influence of pre-exercise massage therapy towards the increase of agility to the football player of Universitas Tunas Pembangunan Surakarta” is declined.